TANGGUNG JAWAB PERDATA NOTARIS ATAS AKTA ANTIDATIR - Rumi Suwardiyati (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2017)
Notary as a public official whose obligation is to make an authentic deed. The deed has a very important role in helping to create legal certainty for the community. The deed also serves as the most perfect evidence. With authentic deeds, the rights and obligations of the parties can be clearly defined so that this is where the legal certainty exists for the community. In making a legal product that is in the form of deed, Notary must be oriented towards Law Number 2 Year 2014 about Notary Position. However, there is also the possibility of any negligence made by a Notary in the making of his act which causes the deed to be doubtful of his authenticity because it does not guarantee the certainty of the date in the making. In this case, the Notary shall be personally liable for the deed of antidathy which is made in the form of compensation in accordance with the loss incurred by the parties or in accordance with the agreement between the parties and the Notary concerned. Such damages can be in the form of money or other matters set by the court. This is because the Notary deliberately makes the deed of antidatir even if the deed is desired or agreed by the parties and the action fulfills the element of the law in the form of negligence caused by the element of error as mentioned in Article 1336 of the Civil Code. Keywords: Notary Public, Civil Liability, Deed of Antidatir.